2003
DOI: 10.1097/01.tp.0000090748.32764.0f
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical bacillus calmette-gueÈrin for the treatment of superficial bladder cancer in renal transplant patients

Abstract: Intravesical BCG in superficial bladder cancer and/or CIS is a valid option, with no added morbidity to renal transplant patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 7 publications
1
48
0
1
Order By: Relevance
“…Some studies have shown that BCG is a viable therapeutic option in patients with high risk non-muscle invasive UCB and concomitant lymphoma, chonic lymphocytic leukemia, treatment with low dose oral steroids, treatment with inhaled steroids, or renal transplant. 101,102 Advanced age, however, is considered a risk factor for complications in patients receiving BCG therapy 103 and there are numerous reports of serious complications of BCG therapy in elderly individuals. 104-108 In a retrospective study of 58 patients, Heiner et al found that the complication rate of BCG therapy was higher in patients older than 70 years (48.6% vs 17.6% for those younger than 70 years) with the peak incidence occurring with the third dose of BCG therapy.…”
Section: Age and Treatment Outcomes Of Non-muscle-invasive Bladdementioning
confidence: 99%
“…Some studies have shown that BCG is a viable therapeutic option in patients with high risk non-muscle invasive UCB and concomitant lymphoma, chonic lymphocytic leukemia, treatment with low dose oral steroids, treatment with inhaled steroids, or renal transplant. 101,102 Advanced age, however, is considered a risk factor for complications in patients receiving BCG therapy 103 and there are numerous reports of serious complications of BCG therapy in elderly individuals. 104-108 In a retrospective study of 58 patients, Heiner et al found that the complication rate of BCG therapy was higher in patients older than 70 years (48.6% vs 17.6% for those younger than 70 years) with the peak incidence occurring with the third dose of BCG therapy.…”
Section: Age and Treatment Outcomes Of Non-muscle-invasive Bladdementioning
confidence: 99%
“…However systemic immunosuppression may not always induce a local immunosuppressive effect, and therefore the bladder immunologic-inflammatory reaction obtained with BCG may maintain its efficacy [27, 37]. While Buzzeo et al [4] refrained from using BCG in immunosuppressed patients, Palou et al [27] reported safe administration of intravesical BCG in 3 renal transplant recipients. It should be noted that while there were no adverse reactions to BCG, all 3 patients were treated with prophylactic isoniazid and rifampin [27].…”
Section: Discussionmentioning
confidence: 99%
“…While Buzzeo et al [4] refrained from using BCG in immunosuppressed patients, Palou et al [27] reported safe administration of intravesical BCG in 3 renal transplant recipients. It should be noted that while there were no adverse reactions to BCG, all 3 patients were treated with prophylactic isoniazid and rifampin [27]. The safe administration of intravesical BCG without concomitant antituberculin prophylaxis has also been reported in 3 immunosuppressed renal transplant recipients [3, 28].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is associated with frequent local and/or systemic adverse effects including BCG sepsis (10,11). The incidence of local and systemic adverse effects is significantly lower with chemotherapeutic agents.…”
Section: Introductionmentioning
confidence: 99%